O ambiente como contexto para o ensino das transformações químicas - Silva, Eliana Eduardo da (2011)
Through the difficulties that were found in the educational process of Chemistry, nowadays, and in a situation which school contents are not related with students life, this study investigated the contributions of problematic situations in the study of chemical transformations based on the CTS proposal. To achieve the propose of this study, some social- scientific questions related to the hydrosphere as a theme for the contextualization of teaching the chemical transformations, based on CTS approach, were presented to the students. A lot of didactic methodologies and proposals were studied in the attempt of looking for an improvement in the process of learning the chemical contexts, through a qualitative search. The students from the second year of high school from ETEC Prof. Alcidio de Souza Prado, attended dialogued classes based on the discussion of some articles from the magazine Quimica Nova na Escola . They joined into two experimental activities (the treatment of water and the production of homemade soap). Those activities went to a presentation of some problematic situations, through a newspaper Jornal do Meio Ambiente (Environment newspaper). The analysis showed that the interaction between students with the subjects studied through the methodologies applied resulted on a better students participation, so the environmental contextualization made easier the understanding of the contents. It was possible to observe that the possibility of students literacy through the development of the conceptual, procedural and attitudinal abilities, gave to the students the opportunity to find out that Science as a human activity.